Challenges and Learning Strategies of Islamic Education in Islamic Boarding Schools in the Industrial Revolution Era 4.0 - Adri Lundeto; Ishak Talibo; Shinta Nento (AL-ISHLAH: Jurnal Pendidikan, 2021)
Along with fast technological advancements, Islamic education problems in Islamic boarding schools are becoming increasingly diversified. They must adapt to technological and digital advancements dubbed the industrial revolution 4.0. When it comes to the fast growth of information technology, the public will constantly question Pesantren's negotiating stance. As a result, it may be appropriate for Islamic boarding schools to loosen their regulations regarding the use of devices or gadgets while maintaining rigorous controls over technology to execute the learning process in the Islamic boarding school setting. This study seeks to ascertain how Islamic boarding schools address the difficulties of the 4.0 revolution period through their educational techniques. This study employs a qualitative approach through the use of a literature review. The findings indicate that Islamic education in pesantren has a substantial impact on educating and moulding the morals of pupils who adhere to the Qur'an and Sunnah. Nonetheless, the needs of the industrial revolution 4.0 era have compelled pesantren to open and develop into institutions as suppliers of Islamic education. Modern Islamic education may address current issues while maintaining the religious principles that define education in the pesantren. This study employs three Islamic teaching principles in Islamic boarding schools: disruptive mentality, self-driving, and reshaping or creation.